Knowledge, attitudes and practices of the general population towards Parkinson’s disease in Meizhou, China: a cross-sectional study - Ying Bian; Peng Diao; Weifeng Liao; Yujiao Lin (BMJ Open)
Objectives This study aimed to assess the general population’s knowledge (K) of Parkinson’s disease symptoms and management, their attitudes (A) towards early detection and treatment, and their health-related practices (P) relevant to prevention and care.Design A cross-sectional study.Setting This study was conducted between February and September 2023 at the Third Affiliated Hospital of Sun Yat-sen University, Yuedong Hospital.Participants This study was conducted among the general population.Primary and secondary outcome measures Demographic information and KAP scores were collected through a self-administered questionnaire.Results A total of 835 valid questionnaires were enrolled, including 445 (53.29%) men. The mean knowledge, attitudes and practices scores were 7.72±2.15 (possible range: 0–13), 30.75±2.74 (possible range: 9–45) and 45.22±5.31 (possible range: 13–65), respectively. Multivariate logistic regression analysis showed that knowledge score (OR=1.12, 95% CI 1.03 to 1.21, p=0.005), attitudes score (OR=1.10, 95% CI 1.03 to 1.18, p=0.002), being female (OR=3.34, 95% CI 2.39 to 4.66, p<0.001), age (p=0.027), lived in an urban setting (OR=2.65, 95% CI 1.00 to 6.98, p=0.048), being a government employee (OR=0.20, 95% CI 0.05 to 0.78, p=0.02) and marital status (p<0.05) were independently associated with proactive practices.Conclusion The general population had inadequate knowledge, suboptimal attitudes and moderate practices towards Parkinson’s disease. It is recommended to implement targeted educational interventions to improve Parkinson’s disease knowledge, especially among those with lower educational attainment and income.